2019
DOI: 10.1038/s41598-019-50623-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional linear modeling of activity data shows analgesic-mediated improved sleep in dogs with spontaneous osteoarthritis pain

Abstract: In humans, pain due to osteoarthritis has been demonstrated to be associated with insomnia and sleep disturbances that affect perception of pain, productivity, and quality of life. Dogs, which develop spontaneous osteoarthritis and represent an increasingly used model for human osteoarthritis, would be expected to show similar sleep disturbances. Further, these sleep disturbances should be mitigated by analgesic therapy. Previous efforts to quantify sleep in osteoarthritic dogs using accelerometry have not dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
(39 reference statements)
0
23
0
1
Order By: Relevance
“…Knazovicky et al 34 examined nighttime activity of companion dogs with osteoarthritis under blinded treatment and placebo conditions; using an owner questionnaire, they found that chronic pain impacts quality of sleep contributing to sleep disturbance. These subjective findings were subsequently supported by actigraphy 38 . With these few latter exceptions, the findings regarding age-or disease-associated changes in daily sleep patterns in dogs have all been conducted on laboratory-housed dogs.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Knazovicky et al 34 examined nighttime activity of companion dogs with osteoarthritis under blinded treatment and placebo conditions; using an owner questionnaire, they found that chronic pain impacts quality of sleep contributing to sleep disturbance. These subjective findings were subsequently supported by actigraphy 38 . With these few latter exceptions, the findings regarding age-or disease-associated changes in daily sleep patterns in dogs have all been conducted on laboratory-housed dogs.…”
mentioning
confidence: 65%
“…The dogs included in this study were considered physically healthy, but were not formally evaluated for conditions that can disrupt sleep, such as chronic pain 34,38 . The SNoRE questionnaire results suggested very little, if any, sleep disturbance, and owners did not report any recent changes in their dogs' sleep; however, this should be considered a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively (or perhaps in combination), total activity may not be the most appropriate outcome measure; the beneficial effects of treatment with frunevetmab may be best characterized by changes in the ability to perform activities, such as jumpingwhich should be reflected in the owner assessments and would not be reflected in changes in activity counts (44). Furthermore, elevations in intensity of activity would not change activity counts, for instance a cat that runs instead of walks or one that climbs and descends the stairs instead of simply walking.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to detect evidence of change in any of the activity categories in our population during either phase of the study. A recent report on functional linear modeling of activity data in dogs showed improvement in sleep in dogs with OA treated with meloxicam compared to placebo in a cross-over design study [ 30 ]. Their conclusions indicate that functional linear modeling is a more sensitive technique for analyzing activity data in dogs than traditional summary techniques.…”
Section: Discussionmentioning
confidence: 99%